The mexican feminist movement and gender studies in the academia (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2019)
Women and gender studies in academic institutions have a recent history(herstory). The first efforts took place in the early 1980’s. The objectiveof this article is to analyze that trajectory, from the link with thefeminist movement. In the first place, some background is analyzed.The organisations that, at the begining of the 20th century, placed atthe centre of the political debate the sufrage and the recognition of women’scitizenship are mentioned. In a second moment, the so-calledfeminist movement of the second wave is analyzed: its main demandsand the dialogue with the State. Finally, three academic experiences aredescribed: El Colegio de México (The College of Mexico), the UniversidadNacional Autónoma de México (National Autonomous University ofMexico) and the Universidad Autónoma Metropolitana unidad Xochimilco(Metropolitan Autonomous University campus Xochimilco). The creationof ad hoc spaces was posible because the feminist movement hadreached enough strength to be a recognised social actor.
Keywords: feminist movement; gender studies; Mexican feminism